Implementation of PJBL-STEM on Disaster Mitigation Sub-Matter to Improve Students' Problem Solving Ability - Lintang Mahardhika; Risa Dwita Hardianti (Journal of Environmental and Science Education, 2025)
The purpose of this study was to determine the difference and level of problem solving ability of students between before and after applying learning with PjBL-STEM on disaster mitigation sub-materials. This research is an experimental research with one group pretest-posttest research design. The data collection methods used are test and documentation methods. The instruments used include pretest and posttest. The data were analyzed descriptively quantitatively. The results obtained are the application of PjBL-STEM on disaster mitigation sub-materials can improve students' problem solving skills. This is indicated by the results of the t-Test which shows the difference in results between before and after the application of PjBL-STEM, as well as the results of the N-Gain test of 0.57 with a moderate category. The level of students' problem solving abilities after implementing PjBL-STEM as a whole is in good criteria. The highest level of students' problem solving abilities is in the indicator of understanding the problem, while the lowest level is in the indicator of devising a plan.